THE SIGNIFICANCE OF TISIKKHĀ AS FOUNDATION OF BUDDHIST CHARACTER EDUCATION IN PROMOTING SUSTAINABLE DEVELOPMENT GOAL 4 - Tri Saputra Medhacitto (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This research examines the significance of Tisikkhā as foundation of Buddhist character education in promoting sustainable development goal 4. Sustainable development is the global effort in creating a better world in the present and future. The United Nations has set seventeen sustainable development goals, addressing the contemporary global challenges. Among the seventeen sustainable goals, the SDG 4 is about the quality of education. Its aim is to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. This goal reflects the significance role of education in promoting sustainable development to address the global challenges. Quality of education in 21st century must adapt to the demands of globalization without neglecting the moral values. Character education is essential in addressing to the moral decline in this modern era. Character education is an approach to education that gives strong attention to the cultivation of positive character such as moral values, ethical behavior, responsibility, honesty and empathy. The character education according Buddhism is grounded in the three pillars or learning (tisikkhā), namely sīla-sikkhā (moral training), samādhi-sikkhā (mental training) and paññā-sikkhā (wisdom training). Tisikkhā is essential in shaping the generations to be compassionate, responsible and ethical individuals in society. Tisikkhā can be an effective way in addressing the current challenges to promote sustainable development goal 4. ABSTRAKPenelitian ini mengkaji signifikansi Tisikkhā sebagai landasan pendidikan karakter Buddhis dalam mendukung pencapaian Sustainable Development Goal (SDG) 4. Pembangunan berkelanjutan merupakan upaya global untuk mewujudkan kehidupan yang lebih baik bagi generasi masa kini dan mendatang. Perserikatan Bangsa-Bangsa telah menetapkan tujuh belas tujuan pembangunan berkelanjutan untuk menjawab berbagai tantangan global kontemporer. Di antara tujuan tersebut, SDG 4 berfokus pada penyediaan pendidikan yang inklusif, adil, dan berkualitas serta mendorong kesempatan belajar sepanjang hayat bagi semua. Tujuan ini menegaskan peran strategis pendidikan dalam mendorong pembangunan berkelanjutan. Kualitas pendidikan pada abad ke-21 dituntut mampu merespons arus globalisasi tanpa mengabaikan nilai-nilai moral. Fenomena kemerosotan moral di era modern menunjukkan urgensi penguatan pendidikan karakter. Pendidikan karakter merupakan pendekatan pendidikan yang menekankan pembentukan nilai-nilai positif seperti integritas, tanggung jawab, kejujuran, empati, dan perilaku etis. Dalam perspektif Buddhisme, pendidikan karakter berakar pada tiga pilar pelatihan (Tisikkhā), yaitu sīla-sikkhā (pelatihan moral), samādhi-sikkhā (pelatihan batin), dan paññā-sikkhā (pelatihan kebijaksanaan). Melalui integrasi ketiga aspek tersebut, Tisikkhā berperan penting dalam membentuk generasi yang berwelas asih, bertanggung jawab, dan beretika. Dengan demikian, Tisikkhā dapat menjadi pendekatan yang relevan dalam menjawab tantangan pendidikan masa kini sekaligus mendukung terwujudnya SDG 4.